Multicentre, randomised, blinded, control trial of drug-eluting balloon vs Sham in recurrent native dialysis fistula stenoses. Issue 3 (May 2019) - Swinnen, Jan "John"; Hitos, Kerry; Kairaitis, Lukas; Gruenewald, Simon; Larcos, George; Farlow, David; Huber, David; Cassorla, Gabriel; Leo, Christopher; Villalba, Laurencia M; Allen, Richard; Niknam, Farshid; et al.
Background: Endovascular treatment of autogenous arteriovenous haemodialysis fistula stenosis has high reintervention rates. We investigate the effect of drug-eluting balloons in the treatment of recurrent haemodialysis fistula stenosis. Methods: This is a randomised, controlled, investigator-initiated and run, prospective, blinded, multicentre trial. Patients with recurrent autogenous arteriovenous haemodialysis fistula stenosis received standard endovascular treatment plus drug-eluting balloon or standard endovascular treatment plus uncoated balloon (Sham). Primary endpoint was late lumen loss in trial area on ultrasound at 6 weeks, 3, 6 and 12 months. Secondary endpoints were freedom from reintervention to the Index Trial Area and decline in fistula flow (Qa). Interim analysis was performed at 6 months (unblinded due to timeliness). Results: Patients with 132 recurrent stenoses (48% in bare Nitinol stents) were randomised with 70 receiving drug-eluting balloon and 62 Sham. At 6 months, decline in late lumen loss was 0.23 ± 0.03 mm/month for Sham and 0.045 ± 0.03 mm/month for drug-eluting balloon arm, a significant difference (0.18 mm, p = 0.0002). At 12 months, this difference persisted at 0.12 mm (p = 0.0003). At 6 months, significant difference in late lumen loss for instent restenoses (p = 0.0004) was observed, with non-significant difference for unstented restenoses (p = 0.065). Mean time for freedom from reintervention was 10.14 months for Sham versus 42.39 months for drug-eluting balloon (p = 0.001). The same was shown for instent (p = 0.014) and unstented (p = 0.029) restenoses. Qa decline rate at 6 months was 36.89 mL/min/month (Sham) and 0.41 mL/min (drug-eluting balloon). The difference was significant (36.48 mL/min; p = 0.02) and persisted to 12 months (p = 0.44). Conclusion: Paclitaxel drug-eluting balloon significantly delays restenosis after angioplasty for recurrent autogenous arteriovenous haemodialysis fistula stenosis, persisting to 12 months. Drug-eluting balloon significantly increases freedom from reintervention at 12 months with these effects true in stented and unstented fistulas.